Activation of polyamine catabolic enzymes involved in diverse responses against epibrassinolide-induced apoptosis in LNCaP and DU145 prostate cancer cell lines - Palavan Unsal, Narçin; Calcabrini, Annarica; Agostinelli, Enzo; Bolkent, Şehnaz; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Springer Wien, Sachsenplatz 4-6, Po Box 89, A-1201 Wien, Austria, 2014)
Epibrassinolide (EBR) is a biologically active compound of the brassinosteroids, steroid-derived plant growth regulator family. Generally, brassinosteroids are known for their cell expansion and cell division-promoting roles. Recently, EBR was shown as a potential apoptotic inducer in various cancer cells without affecting the non-tumor cell growth. Androgen signaling controls cell proliferation through the interaction with the androgen receptor (AR) in the prostate gland. Initially, the development of prostate cancer is driven by androgens. However, in later stages, a progress to the androgen-independent stage is observed, resulting in metastatic prostate cancer. The androgen-responsive or -irresponsive cells are responsible for tumor heterogeneity, which is an obstacle to effective anti-cancer therapy. Polyamines are amine-derived organic compounds, known for their role in abnormal cell proliferation as well as during malignant transformation. Polyamine catabolism-targeting agents are being investigated against human cancers. Many chemotherapeutic agents including polyamine analogs have been demonstrated to induce polyamine catabolism that depletes polyamine levels and causes apoptosis in tumor models. In our study, we aimed to investigate the mechanism of apoptotic cell death induced by EBR, related with polyamine biosynthetic and catabolic pathways in LNCaP (AR+), DU145 (AR-) prostate cancer cell lines and PNT1a normal prostate epithelial cell line. Induction of apoptotic cell death was observed in prostate cancer cell lines after EBR treatment. In addition, EBR induced the decrease of intracellular polyamine levels, accompanied by a significant ornithine decarboxylase (ODC) down-regulation in each prostate cancer cell and also modulated ODC antizyme and antizyme inhibitor expression levels only in LNCaP cells. Catabolic enzymes SSAT and PAO expression levels were up-regulated in both cell lines; however, the specific SSAT and PAO siRNA treatments prevented the EBR-induced apoptosis only in LNCaP (AR+) cells. In a similar way, MDL 72,527, the specific PAO and SMO inhibitor, co-treatment with EBR during 24 h, reduced the formation of cleaved fragments of PARP in LNCaP (AR+) cells.
Keywords: Epibrassinolide; Polyamines; Apoptosis; Prostate cancer; Oxidation-Products; Spermidine/Spermine N-1-Acetyltransferase; Brassinosteroids; Arabidopsis; Inhibition; Mechanism; Oxidase; Kinase